Nowa jakość kształcenia akademickiego w sytuacji zmiany cywilizacyjnej – interaktywny wykład problemowy - MORAŃSKA, DANUTA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Danuta Morańska, Nowa jakość kształcenia akademickiego w sytuacji zmiany cywilizacyjnej – interaktywny wykład problemowy [The new quality of academic education in the face of a civilisation change – the interactive problem-focused lecture]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 221-234. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.13 The article presents important problems that colleges and universities will have to face in order to adapt its didactic offer to the requirements of the present day. The article is based on the research conducted by the author during the training of the researchers and teachers at one of the Polish technical universities.